Identification, characterization and degradation studies of polycyclic aromatic hydrocarbons in recreational urban lakes, road dusts and road side soils of Kuala Lumpur city, Malaysia / Nur Aainaa Syafini binti Mohd Radzi - Mohd Radzi, Nur Aainaa Syafini (2013)
This study is on the distributions and concentrations of 16 polycyclic aromatic hydrocarbons (PAHs) in eleven surface water, suspended particulate matter (SPM) and surface sediments samples collected from two urban recreational lakes namely, Taman Jaya and Lake Perdanas in Kuala Lumpur city. The total PAH concentrations of Lake Taman Jaya and Lake Perdana ranged from 0.56- 1.19 μg L-1 and 0.32- 1.30 μg L-1 in surface water, 0.93- 2.80 μg g-1 and 1.21-2.92 μg g-1 in SPM, and 0.15– 0.23 μg g-1 and 0.01– 0.27 μg g-1 in surface sediments respectively. High molecular weight (HMW) PAHs dominates the distribution of PAHs suggesting a great influence of pyrogenic activities. The ratio of Phen/Anth to Flt/ Pyr suggests that the major sources of PAHs in Lake Taman Jaya and Lake Perdana were from both petrogenic and pyrogenic sources. The levels of PAHs in both lakes are relatively higher in surface waters and SPM, and lower in surface sediments, in comparison to those reported around the world. The calculation of TEQcarc in surface sediments of both lakes shows that it was low compared to other previous studies worldwide. On the other hand, studies on PAHs in road dust and road side soil samples of Kuala Lumpur city shows that road dust of the residential areas (9.25- 689 μg g-1 dw) were highly polluted with PAHs compared to the industrial (1.30- 33.2 μg g-1 dw) and commercial areas (23.3- 571 μg g-1 dw). Meanwhile, the results for road side soil samples shows that PAHs in commercial areas (15.7- 1593 μg g-1 dw) were more polluted with PAHs than the industrial (0.387- 36.5 μg g-1 dw) and residential areas (0.119- 180 μg g-1 dw). High molecular weight PAHs dominates studied areas with pair ratios calculation of Phen/ Anth to Flt/ Pyr shows that the major cause of these PAHs pollutions came from pyrogenic activities. iii A study on identification of natural capability in degrading PAHs has also been conducted. A few isolated bacteria from termite fungal comb and contaminated road side soil have been selected and grouped for the degradation study. Among the nine single PAHs tested, only fluoranthene and pyrene shows positive sign of degradation against the applied bacteria consortium. One degradation product has been detected from degradation of fluoranthene by bacteria consortium isolated from termite fungal comb (1-butyl-8- methyl-1,8a-dihydronaphthalene) while two degradation products has been detected from degradation by bacteria consortium from road side soil (1-vinyl-9H-fluorene and 9- methylene-1-vinyl-9H-fluorene). Meanwhile, the degradation of pyrene by bacteria consortium from termite fungal comb and road side soil has produced three (1,10adihydropyrene, 9-ethyl-1-methyl-1H-phenalene and 2-ethyl-1-isopropyl-8-methyl- 1,2,3,4,4a,8a-hexahydronaphthalene) and four (1,10a- dihydropyrene, 9-ethyl-1-methyl-1Hphenalene, 2-ethyl-1-isopropyl-8-methyl-1,2,3,4,4a,8a-hexahydronaphthalene and 7-butyl- 1-methyl-1,2-dihydronaphthalene) degradation products, respectively. Overall, the degradation of fluoranthene and pyrene by the selected bacteria consortium increased with time but the degradation process is considered slow. Degradation by bacteria consortium from contaminated road side soil was found to be more effective than bacteria consortium from termite fungal comb.